Effect of Piriformospora indica-Induced Systemic Resistance and Basal Immunity Against Rhizoctonia cerealis and Fusarium graminearum in Wheat - Li, Liang; Guo, Nannan; Feng, Yu; Duan, Mengmeng; Li, Chunhui (Frontiers in Plant Science, 2022)
Wheat is among the ten top and most widely grown crops in the world. However, wheat is often infected with many soil-borne diseases, including sharp eyespot, mainly caused by the necrotrophic fungus Rhizoctonia cerealis, and Fusarium head blight (FHB), caused by Fusarium graminearum, resulting in reduced production. Piriformospora indica is a root endophytic fungus with a wide range of host plants, which increases their growth and tolerance to biotic and abiotic stresses. In this study, capability of P. indica to protect wheat seedlings against R. cerealis and F. graminearum was investigated at the physiological, biochemical and molecular levels. Our results showed that P. indica significantly reduced the disease progress on wheat caused by F. graminearum and R. cerealis in vivo but not showed any antagonistic effect on F. graminearum and R. cerealis in vitro. Additionally, P. indica can induce systemic resistance by elevating H2O2 content, antioxidase activity, relative water content (RWC) and membrane stability index (MSI) compared to the plants only inoculated with F. graminearum or R. cerealis and control. RNA-seq suggested that transcriptome changes caused by F. graminearum were more severe than those caused by R. cerealis.The number of differentially expressed gene (DEGs) in the transcriptome can be reduced by the addition of P. indica: for F. graminearum reduced 18% and for R. cerealis reduced 58%. The DEGs related to disease resistance such as WRKY and MAPK were up-regulated by P. indica colonization.The data further revealed that the transcriptional resistance to F. graminearum and Rhizoctonia cerealis mediated by P. indica is quite different.